Integrative computational analysis of plant-derived flavonoids as inhibitors of Listeriolysin O and Internalin A in Listeria monocytogenes - Shahadul Hassan Sourav; Noimul Hasan Siddiquee; Rahnuma Tabassum; Lamia Islam; Syed Kashif Zaidi; Mohammad Sharif Uddin; Sumita Rani Saha; Imam Hossain (PLoS ONE, 2026)
Foodborne pathogen Listeria monocytogenes causes listeriosis, a rare but deadly condition. Internalin A ( InlA ) and Listeriolysin O ( LLO ), its main virulence factors, facilitate adhesion, invasion, intracellular survival, and intercellular spreading, making them interesting therapeutic targets. L. monocytogenes infections are becoming harder to treat because of antibiotic resistance; hence, flavonoids are being considered. An integrated in-silico technique was used to test plant-derived flavonoids’ inhibitory efficacy against these proteins. For both targets, three modes of docking (HTVS, SP, and XP docking) were used for the preliminary screening from a library of 1,254 flavonoids. While CIDs 441667, 15126294, and 187808 showed favorable in-silico profiles for InlA with scores of −8.461, −7.578, and −7.521 kcal/mol, respectively, CIDs 441699, 443648, and 442868 showed the best affinity for LLO with values of −7.446, −5.991, and −5.852 kcal/mol, respectively. Admet analysis predicted the drug-likeness and safety characteristics of the compounds. Subsequently, the QM calculation was employed to examine the interaction of these compounds with the receptor, alongside their MEP and NBO characteristics. The selected ligands and the control ampicillin for both proteins were utilized to build protein-ligand complexes, subsequently assessed via a 100 ns molecular dynamics simulation. Subsequent post-simulation MM-GBSA, PCA and DCCM analysis of the trajectories evaluated their dynamic stability concerning InlA and LLO . CIDs 441667 and 15126294 for InlA , as well as CIDs 441699 and 443648 for LLO , have been identified as potential inhibitors, establishing a basis for future in vivo investigations and experimental validation.